Early career clinicians' supervision experiences related to secondary traumatic stress when treating child survivors of sexual abuse. Issue 2 (2nd July 2020) - Wymer, Brooke; Guest, Jessie D.; Deaton, Jennifer D.; Newton, Therese L.; Limberg, Dodie; Ohrt, Jonathan H.
ABSTRACT: In this study, we examined experiences of supervision related to Secondary Traumatic Stress responses among early career mental health clinicians treating child survivors of sexual abuse. We utilized consensual qualitative research methodology to capture the experiences of clinicians undergoing the phenomena. We report data analysis findings and implications for research and clinical supervisors.